Adoption of blockchain technology to improve Halal supply chain performance and competitiveness - Hendayani, Ratih; Fernando, Yudi (Emerald Publisher, 2023)
This study aims to investigate the relationship between blockchain technology adoption and firm competitiveness through Halal supply chain performance as a mediating variable. This paper has used the explanatory approach and multivariate data analysis using partial least squares with structural equation modelling. The data were collected from 178 Indonesian manufacturing firms producing Halal-certified foods and beverages. The findings reveal that adopting blockchain technology positively and significantly affects Halal supply chain performance and firm competitiveness. The total indirect effect shows that the availability of blockchain technology indirectly affects the firm’s competitiveness through Halal supply chain performance. This study has provided a novel theoretical framework showing that adopting blockchain technology can improve the Halal supply chain performance and the firm’s competitiveness. The transparency and integrity features of blockchain technology have strengthened consumers’ confidence in the reliability of Halal-certified food and beverage products.